The Effect of Marketing MIX Strategy on Purchasing Decisions for Groceries at Moga Sukses Jerowaru Store - Masfian Eva Zulhalifi; Junaidi Sagit; Rusminah, Rusminah; Rita Alfin; Listiyana, Listiyana (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This study aims to determine whether or not there is an influence of the Marketing MIX Strategy on the decision to purchase groceries at Toko Moga Sukses. The type of research used is causal associative research with a quantitative approach. The data collection method used is the survey method using primary data collected directly from respondents using a questionnaire. The population in this study were Jerowaru residents who were found buying groceries at the Moga Success store. with a research sample of 80 people. Sampling using probability sampling with convenience sampling technique. The analytical tool used is Multiple Linear Regression using SPSS V26. Based on the variables used, the analysis results show that: (1) Product variables have a positive and significant influence on purchasing decisions at successful moga stores (2) Price has a positive and significant influence on purchasing decisions at successful moga stores (3) Distribution has a positive and significant influence on purchasing decisions at successful moga stores (4) Promotion has a positive and significant influence on purchasing decisions at successful moga stores.